Constraint Propagation for Analog and Mixed-Signal Integrated Circuit Design: - Andreas, Krinke (VDI Verlag, 2020)
While the design of digital integrated circuits (ICs) is largely automated, the design of analog/ mixed-signal (AMS) ICs is still dominated by manual tasks. One of the biggest obstacles to further automation is the large number of constraints that have to be taken into account during AMS IC design. They are derived both from the specifcation and during the actual design process and must be fulflled before production of the IC can begin. The aim of this work is to present our fndings regarding the formalization of constraints and their propagation within the design hierarchy in order to make them visible and verifable in all relevant cells. Constraints are integrated into the AMS IC design process so that they can be considered at all stages of the design. Our research enables the integration and consideration of constraints in all types of design tools—not only for AMS IC design, but after generalization for any design process.ContentsAbbreviationsVIIISelected SymbolsX...